2007
DOI: 10.1016/s0968-8080(06)29280-2
|View full text |Cite
|
Sign up to set email alerts
|

The Commodification of Obstetric Ultrasound Scanning in Hanoi, Viet Nam

Abstract: Growing numbers of pregnant women across the world now routinely have ultrasound scans as part of antenatal care, including in low-income countries. This article presents the findings of anthropological research on the use of obstetric ultrasonography in routine antenatal care in Hanoi, Viet Nam. The findings come from observation, a survey and interviews with women seeking ultrasound scans at a main maternity hospital and interviews with doctors providing ultrasound there. We found a dramatic overuse of ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 11 publications
5
113
1
1
Order By: Relevance
“…This overuse of obstetric sonography was reported by Mubuuke et al [22] in an earlier study. Gammeltoft and Nguyen [26] as well as Tautz et al [27] have almost reported similar reasons for the overuse of obstetric sonography in other parts of the world. However, it should be advanced that such routine imaging adds significant costs to the women and may not yield any more valuable information as thought.…”
Section: Possible Reasons For the Many Obstetric Scansmentioning
confidence: 81%
“…This overuse of obstetric sonography was reported by Mubuuke et al [22] in an earlier study. Gammeltoft and Nguyen [26] as well as Tautz et al [27] have almost reported similar reasons for the overuse of obstetric sonography in other parts of the world. However, it should be advanced that such routine imaging adds significant costs to the women and may not yield any more valuable information as thought.…”
Section: Possible Reasons For the Many Obstetric Scansmentioning
confidence: 81%
“…In this changing scenario, there has been a shift towards greater use of higher level reproductive health services, both because they have more to offer, e.g. ultrasound scans, 26 and due to the lack of referral functions at the CHS level.…”
Section: Discussionmentioning
confidence: 99%
“…Obstetric ultrasound has become an indispensable part of ANC around the world [5], although ultrasound imaging may not be universally available in low-resource settings [6]. Ultrasound during pregnancy is generally used to estimate gestational age, number of foetuses, placental localisation, screening of foetal malformation, foetal growth and foetal presentation [7,8].…”
Section: Introductionmentioning
confidence: 99%